已知a^3X=1/27,求a^2x+ a^-2 x/a^x+a^-x的值
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 06:10:59
已知a^3X=1/27,求a^2x+a^-2x/a^x+a^-x的值已知a^3X=1/27,求a^2x+a^-2x/a^x+a^-x的值已知a^3X=1/27,求a^2x+a^-2x/a^x+a^-x
已知a^3X=1/27,求a^2x+ a^-2 x/a^x+a^-x的值
已知a^3X=1/27,求a^2x+ a^-2 x/a^x+a^-x的值
已知a^3X=1/27,求a^2x+ a^-2 x/a^x+a^-x的值
a^3x=1/27
a^x=1/3
a^2x+ a^-2 x/a^x+a^-x
=(a^2x+1/a^2x)/(a^2+1/a^x)
=[(a^4x+1)/a^2x]/[(a^2x+1)/a^x]
=(a^4x+1)/a^x(a^2x+1)
=(1/81+1)/[1/3*(1/9+1)]
=41/15
已知a^3X=1/27,求a^2x+ a^-2 x/a^x+a^-x的值
已知a^3X=1/27,求a^2x+ a^-2 x/a^x+a^-x的值
已知a^2x=根号2+1,求(a^3x+a^-3x)/(a^x+a^-x)
已知a^(2x)=根号2-1,求a^(3x)+a^(-3x)/a^x+a^(-x)
已知a^2x=根号2+1求(a^3X+a^-3X)/(a^X+a^-X)
已知a^2x=2(a>0且a不等于1),求(a^3x)+(a^-3x)/(a^x)+(a^-x)的值
已知a^2x=2(a>0,且a≠1),求 a^3x+a^(-3x)/ a^x+a^(-x)的值
已知a^2x=2/3,求(a^3x+a^-3x)/(a^x+a^-x)的值
已知a^5*a^x+2*a^2x-1=a^27,求x的值.
★已知a>0,a^2x=2根号2+3,求a^6x+a^-6x/a^x-a^-x的值★已知a>0,a^2x=2√2+3,求a^6x+a^-6x/a^x-a^-x的值.应该先把a^6x+a^-6x/a^x-a^-x化简吧.
1.已知x+1/x=4求x^3+x^-3的值 2.已知a^(2x)=根号2 -1,求[(a^3x)-(a^-3x)]/(a^x-a^-x)的值
已知a^(2x)=(根号2)+1,求(a^3x+a^-3x)/(a^x+a^-x)的值
已知a^2x=根号2+1,求(a^3x+a^-3x)/(a^x+a^-x)的值
已知a^2x=√2-1,求(a^3x-a^-3x)/(a^x-a^-x)的值
已知x^a=1/√3+√2,求代数式,x^4a-x^-4a/x^a-x^-a的值
已知x^a=1/(根号3+根号2),求代数式x^4a-x^-4a/(x^a-x^-a)的值
已知(x^2-x+1)^3=a⑥x^6+a⑤ x^5+a④ x^4+a③x^3+a②x^2+a①x+a⓪求:(1)a⑥+a⑤ +a④+a③+a②+a①+a⓪=(2)a⑥+a④+a②+a⓪=
数学题 已知2X-3/(X-1)(X+2)=A/x-1+B/x+2,求A,B